Characterization of arabinogalactan-rich mucilage from Cereus triangularis cladodes. (20th August 2015) - Petera, B.; Delattre, C.; Pierre, G.; Wadouachi, A.; Elboutachfaiti, R.; Engel, E.; Poughon, L.; Michaud, P.; Fenoradosoa, T.A.
Highlights: High yield polysaccharides extraction from Cereus triangularis cladodes. Arabinogalactan from Cereus triangularis cladodes with Ara f /Gal p = 0.67 ratio. High molecular weight mucilage from Cereus triangularis cladodes. Antioxidant properties of arabinogalactan. Abstract: Cereus triangularis (Cactaceae) is a cactus used in food decoction as a traditional medicine in the North region of Madagascar to reduce stomach ache and intestinal diseases. Hydrocolloids were sequentially extracted from its cladodes with a yield of 24% (240 mg/g based on dried cladodes powder). Structural analyses has revealed that this polysaccharide with a molecular mass of 8430, 000 g/mol was mainly composed of a galactan backbone of a (1 → 4) linked β -d -Gal p residues probably substituted at position 3 byl -arabinofuranosyl residues. In vitro antioxidant activity of this arabinogalactan-rich fraction was detected and quantified by radical DPPH scavenging, hydroxyl radical scavenging, radical anion superoxide scavenging and reducing power method.